Cognitive Process Development in Primary School Age Children with Different Types of Ontogenesis. Course of correction. - Maksimenko M.You; Shal L. (Moscow State University of Psychology and Education, 2018)
The psychologists admit the frequent infantilism of the emotional and personal sphere in children of primary school age. Presented infantilism may occur in the form of difficulties in differentiating of emotional states and understanding the causes of one's own actions and peers actions which may lead to problems in behavior and interpersonal relationships. Section 3 of the correctional course presents tasks aimed to the development and formation of an emotional and personal sphere in children of primary school age within the framework of the cognitive approach - a verbal and nonverbal understanding of emotions and emotional expression. Phenomenological approach to the study of the emotional sphere of the child is extremely heterogeneous and inaccurate, since in the emotional sphere there are many different aspects of emotions and emotional states are singled out, and therefore their differentiation is ambiguous. Continuation. Вeginning in No 1 (54), 2017